2014
DOI: 10.3168/jds.2014-8162
|View full text |Cite
|
Sign up to set email alerts
|

Effects of duration of moderate increases in grain feeding on endotoxins in the digestive tract and acute phase proteins in peripheral blood of yearling calves

Abstract: Effects of duration of grain feeding on the concentration of endotoxic lipopolysaccharide (LPS) in digesta throughout the digestive tract and on acute phase proteins and LPS in peripheral blood were determined in Holstein yearling calves. Twenty-five Holstein yearling steer calves received either a forage-based diet containing 92% hay and 8% of a mineral and vitamin pellet on a dry matter basis (CON) or a moderate-grain diet, obtained by replacing 41.5% of the hay in the forage-based diet with barley grain, fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 37 publications
1
20
0
Order By: Relevance
“…For instance, a decrease in the ruminal fluid pH increases the activity of LPS in the ruminal fluid, and the concentration of SAA (Gozho, Krause, & Plaizier, ; Gozho et al., ; Khafipour, Krause, & Plaizier, 2009a), Hp (Gozho et al., , ; Khafipour et al., 2009a), and LBP (Khafipour et al., 2009a) in the blood. However, it has also been reported that an increase in the activity of LPS in the ruminal fluid does not affect the blood concentration of the SAA, Hp, and LBP (Khafipour, Krause, & Plaizier, 2009b; Plaizier et al., ). These inconsistent findings regarding the relationship between LPS activity in the ruminal fluid and acute‐phase protein concentrations in the plasma may be due to the differing individual responses of rumen fluid LPS activity to the same feed (Hirabayashi et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, a decrease in the ruminal fluid pH increases the activity of LPS in the ruminal fluid, and the concentration of SAA (Gozho, Krause, & Plaizier, ; Gozho et al., ; Khafipour, Krause, & Plaizier, 2009a), Hp (Gozho et al., , ; Khafipour et al., 2009a), and LBP (Khafipour et al., 2009a) in the blood. However, it has also been reported that an increase in the activity of LPS in the ruminal fluid does not affect the blood concentration of the SAA, Hp, and LBP (Khafipour, Krause, & Plaizier, 2009b; Plaizier et al., ). These inconsistent findings regarding the relationship between LPS activity in the ruminal fluid and acute‐phase protein concentrations in the plasma may be due to the differing individual responses of rumen fluid LPS activity to the same feed (Hirabayashi et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Ruminal pH is reduced lower than 5.8 during SARA due to the decreased in the abundances of cellulolytic bacteria and the increased in the proportions of starch-fermenting and lactic acid producing bacteria [2]. The lower pH in the rumen content may enhance the lysis of gram-negative bacteria which is accompanied with increasing ruminal free lipopolysaccharide (LPS) [3]. However, following the rumen epithelial barrier failed in a low-pH rumen condition, LPS may be translocated into the interior circulation of the body and triggered systemic inflammation by promoting the release of pro-inflammatory cytokines, such as tumor necrosis factor (TNF)-α, interleukin (IL)-1β and IL-6 [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…CON: basal diets without supplement; LBS: basal diets low supplemented with 0.25 g of BSS/kg of DMI; MBS: basal diet medium supplemented with 0.5 g of BSS/kg of DMI; HBS: basal diet high supplemented with 1 g of BSS/kg of DMI. 2 SEM, standard error of the mean 3. OTU, operational taxonomic units 4.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, overfeeding cows with grain-rich diets results in several disorders such as SARA and liver abscesses (Emmanuel et al, 2008). Feeding high amounts of rapidly fermenting carbohydrates decreased rumen pH, altered rumen microbial population, and increased concentrations of endotoxin (LPS) in rumen fluid (Khafipour et al, 2009;Plaizier et al, 2014). The altered ruminal LPS and pH could act synergistically to disrupt barrier function (Emmanuel et al, 2007), and once the epithelium has been breached, mucosa-associated lymphoid tissue cells respond by triggering local inflammation via LPS/toll-like receptor 4 (TLR4) signaling Thiamine supplementation facilitates thiamine transporter expression in the rumen epithelium and attenuates high-grain-induced inflammation in low-yielding dairy cows X. H. Pan,* † L. Yang,* Y. Beckers, † F. G. Xue,* Z. W. Tang,* L. S. Jiang, ‡ 1 and B. H. Xiong* 1 pathway, and the pro-inflammatory cytokines would be excessively produced (Kurashima et al, 2013;Zhang et al, 2016).…”
Section: Introductionmentioning
confidence: 99%